Point‐of‐care testing facilitates screening and treatment for anaemia in women and children in rural Pakistan. (6th November 2017) - McCormack, Tessa; Ayub, Rukhsana; Aziz, Faisal; Motta, Lara; Spaeth, Brooke; Shephard, Mark
Abstract: Objective: To use point‐of‐care testing to screen and facilitate treatment for anaemia and to establish an estimate of the prevalence of anaemia in the local population. Design: An uncontrolled before and after study design was used to evaluate the effectiveness of the intervention on the anaemia status of participants. Setting: This study took place in a rural mountain community (population approximately 1000) in the Haripur district in northern Pakistan. Participants: Women of child‐bearing age (15–49 years) and children (12–14 years) were included in this study. Interventions: The intervention included point‐of‐care testing for haemoglobin, treatment with mebendazole and oral iron supplementation, and an education campaign about anaemia delivered by community health workers and medical students. Main outcome measures: The main outcome measure was an increase in blood haemoglobin over the study period. A secondary outcome measure was a positive change in anaemia status or classification post‐intervention. Results: Anaemia was initially detected in 64 (53%) women and 15 (47%) children. The mean haemoglobin concentration increased significantly ( P < 0.001) from 118 to 130 g L −1 (women) and 120 to 130 g L −1 (children) post‐intervention. Overall prevalence of anaemia in women ( P < 0.001) and children ( P < 0.001) decreased significantly (by 30% and 34%, respectively) post‐intervention. Conclusions: Point‐of‐care testing used for the detection of anaemia in this rural community helped to identify the burden of disease and to reduce this significantly by way of rapid diagnosis, education and immediate medical intervention.